Erotyka w grach cyfrowych. Cenzura i autocenzura wątków erotycznych w przekazach digitalnych - SIKORSKA, JOANNA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Eroticism in digital games. Censorship and self-censorship of erotic themes in digital communication The aim of the article is to illustrate the issue of eroticism in video-games in the context of censorship that was in use in its reference. The purpose of a brief history of sexuality in digital communications, as well as an analysis of most important games in the thematic area is to draw attention to the ways in which censorship and self-censorship function in games of a sexual nature. One of the most important elements is also an analysis of existing rating systems and an indication of how censorship practices affect the ways erotic games and, in a broader sense, on game poetics are presented.